How is Students’ Proportional Reasoning Based on Idealist Personality Type in Senior High School? - Ramlan, Andi Mariani; Budayasa, I Ketut; Rahaju, Endah Budi (Journal of Posthumanism, 2025)
Proportional reasoning and personality types play a vital role in mathematics education, as they relate to both science and mathematical learning across all grade levels. Understanding students’ personality types early on offers valuable insights that can guide tailored instructional strategies. However, there remains a lack of research specifically examining the relationship between proportional reasoning and idealist personality types. This research investigates how students with idealist personality traits apply proportional reasoning when solving problems involving trigonometric ratios. Employing a case study methodology with a qualitative descriptive framework, the participants were selected according to carefully defined criteria aligned with the study’s aims. Data processing involved applying proportional reasoning, drawing from both the subjects’ task performance and task-based interviews. Valid data were systematically analyzed through classification, reduction, presentation, interpretation, and conclusion stages. The findings revealed that students with an idealist personality type were capable of solving mathematical problems and comprehending concepts such as covariation, ratios, proportions, and cross-multiplication strategies. A calculation error occurred during the procedure, resulting in a correct final answer despite an inaccurate initial step. Idealist personality type can solve proportional problems even if there are incorrect steps. There are still proportional reasoning activities that are not yet visible. Next, these findings can offer valuable insights for future studies focusing on the design of targeted learning approaches, the selection of innovative teaching models and learning media tailored to the characteristics of idealist students, specific mathematical topics, and the development of learning strategies for other personality types.